Perhitungan Pensiun Normal pada Dana Pensiun Menggunakan Projected Unit Credit - Aprijon M.Ed (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2020)
The development of the business world increases the field and competition of job seekers. Efforts made by employers for the sake of retaining their employees one of them follows pension fund insurance which aims to establish a number of funds so that they can be used after entering retirement age. The method used in this study is the Projected Unit Credit method. Based on the results of this study it was found that the salary and salary increase level of participants in the pension fund while working were very influential in the calculation of pension funds, namely the greater salary and rate of salary increase, the greater the contribution fees that must be paid by participants to the company and also the greater the value of the obligations will be paid by the company to pension fund participants. Keywords: Projected Unit Credit Method, Normal Pension Fund, Salary